1983
DOI: 10.1007/bf00927421
|View full text |Cite
|
Sign up to set email alerts
|

Identification of surface and internal antigens from spontaneously releasedPlasmodium falciparum merozoites by radio-iodination and metabolic labelling

Abstract: Spontaneously released merozoites from synchronous Plasmodium falciparum cultures were isolated in the presence of protease blocker. 1-5 X 10(10) merozoites were obtained in each experiment. The isolated merozoites possessed a thick surface coat and about 80% were invasive to human erythrocytes although they did not subsequently develop into ring stages. Tests using several analytical methods showed the merozoite preparations to be free of any erythrocyte contamination. Six labelled proteins were identified af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Intact erythrocytes from synchronized cultures at 8-12% parasitemia, containing ring-, trophozoite-, or schizont-stage parasites were surface labeled with 125I using lactoperoxidase (15). Freshly-collected merozoites were surface labeled with 125I by a modified lactoperoxidase procedure (16).…”
Section: Methodsmentioning
confidence: 99%
“…Intact erythrocytes from synchronized cultures at 8-12% parasitemia, containing ring-, trophozoite-, or schizont-stage parasites were surface labeled with 125I using lactoperoxidase (15). Freshly-collected merozoites were surface labeled with 125I by a modified lactoperoxidase procedure (16).…”
Section: Methodsmentioning
confidence: 99%
“…MSA 2, the second main molecule present on the Plasmodium falciparum merozoite surface, is a 35–56 kDa glycoprotein whose size and isoelectric point vary according to the parasite strain (1, 2). It is expressed during the late ring stage (≈ 12 h after merozoite invasion) and its maximal concentration is observed 42 h after invasion (3, 4). This antigen has been found to be associated with internal membranes in very mature multinucleated schizonts; it is present on the merozoite surface and residual bodies of all P. falciparum strains studied to date (5–9).…”
mentioning
confidence: 99%
“…Merozoites of P. falciparum (Colombianstrain FCB-I, originally isolated by C. Espinai, Instituto Nacional de Saiud, Bogota, and obtained from K. Rieckman, University of New Mexico, Albuquerque) were prepared according to the procedure of Mrema et ai. [16] and Heidrich et aL [41]. Briefly, highly synchronous cultures of asexual parasites [67,68] were obtained by alternate applications of the Sorbital and the Plasmagel [29,32,42,52] procedures.…”
Section: Merozoites Metabolic and Surface Radiolabellingmentioning
confidence: 99%
“…It has been shown that most of the merozoite surface antigens stem from a high molecular weight glycoprotein precursor of 185-195 kDa present in schizonts [13,19,20,46]. During maturation of schizonts to merozoites, this precursor is processed to various smaller proteins which are then found on the merozoite surface [11,16]. Surface radiolabelling of purified merozoites has shown the protein composition of the outer surface to be relatively simple ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation